Nanocomposite of nickel oxide nanoparticles and polyethylene oxide as printable hole transport layer for organic solar cells. Issue 6 (11th April 2019) - Ruscello, Marta; Sarkar, Tanmoy; Levitsky, Artem; Matrone, Giovanni Maria; Droseros, Nikolaos; Schlisske, Stefan; Sachs, Eleni; Reiser, Patrick; Mankel, Eric; Kowalsky, Wolfgang; Banerji, Natalie; Stingelin, Natalie; et al.
Abstract : Low temperature NiO x is achieved using PEO as sacrificial ink additive to make hole transport layer for solar cells. Abstract : We focused on the low-temperature fabrication (∼100 °C) of nanoparticle-based NiO x hole transport layers for organic solar cells. We used high molecular weight polyethylene oxide (PEO) as a sacrificial additive for the processing of NiO x nanoparticle (NP) dispersions which is removed from the film by oxygen plasma prior to the active layer deposition. Through comprehensive characterization by optical, electrical and scanning probe techniques we show that an optimal NiO x  : PEO ratio allows to disperse the NPs, hindering their aggregation and maximizing device performance. Finally, we demonstrate the practical relevance of our approach by inkjet printing the NiO x :PEO blends to produce hole transport layers (HTLs) for P3HT:PCBM bulk heterojunction solar cells with comparable efficiencies to devices produced with high-temperature precursor-based approaches. The utilization of P3HT:PCBM as active layer material is meant to offer an optimum standard for the introduction of the presented HTL processing approach and its applicability to a wider range of hybrid systems and multilayer optoelectronic devices.